Interventional Radiologic Management for Chylothorax. Issue 1 (January 2015) - De Boo, Diederick W.; Mott, Nigel; Lyon, Stuart M.
<x xml:space="preserve">Abstract</x> Chylothorax is an uncommon type of pleural effusion. Causes include iatrogenic, blunt/sharp chest trauma, and mediastinal neoplasms. Low-output chylothoraces (<1000 mL/d) tend to heal and respond well to conservative management, which facilitates the spontaneous healing of the chyle leak. High-output chylothoraces usually fail conservative management and require some form of invasive treatment. Surgical treatment can be challenging due to the patients' condition and variations in thoracic duct anatomy. Percutaneous treatments performed by interventional radiologists have proven to be successful and are minimally invasive. This article describes the etiology and treatment options for chylothorax with a focus on interventional radiologic management.